Методика диагностики понимания неопределенности жизненных ситуаций и совладания с ними - Татьяна Петровна Бутенко (Психология. Журнал Высшей школы экономики, 2011)
The article describes the experience of usage of a measure designed to investigate understanding of uncertainty in life situations as an integral phenomenon with its own mechanisms. A measure is designed to ask participants to generate situations with uncertainty on the basis of given stimulus situations. The participants' texts obtained in the study were analyzed within the framework of qualitative approach and «grounded theory» method. Several versions about phenomenon's nature have been proposed as a result, one of the versions is presented in the article.